Toxic Positivity: The Pressure to Always Feel Happy as a Health Care Worker and How to Deal with a Negative Review in The Hospital Workplace. The Importance of Mentoring - Michailidou, Evangelia Michail (British Journal of Healthcare and Medical Research, 2023)
Toxic positivity: It sounds paradoxical, even absurd. How is it possible that the word positivity, intertwined with concepts such as joy and happiness, is defined by the adjective toxic? And yet, in the age of social media, this framework is spreading more and more. Thus, a whole culture of this toxic behavior is created. Phrases like “Good Vibes Only”, “Just think positive”, “Everything happens for a reason” are constantly recycled. The phenomenon is of course magnified by technology, but it also exists beyond that.